2019
DOI: 10.7196/sajch.2019.v13i3.1570
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding knowledge and practices among mothers of children younger than 2 years from a rural area in the Limpopo province, South Africa

Abstract: Appropriate feeding practices during infancy and early childhood are critical for a child's growth and development. [1,2] Breastfeeding provides optimal and complete nutrition during the first 6 months of a baby's life, offers immunologic benefits to the baby and contributes to the psychological relationship between the mother and child. [3,4] The World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) therefore recommend that mothers breastfeed exclusively for the first 6 months of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…The post-2010 period (Table 3 ) after South Africa endorsed the 2010 WHO infant feeding guidelines for HIV-positive women recommending EBF for 6 months irrespective of HIV status resulted in a wide range of EBF rates among HIV-positive (26–99%) and HIV-negative (12–92%) women [ 64 69 ]. However, EBF duration was brief (1-3 months) [ 66 , 70 , 71 ]. While initiation of breastfeeding was high, there were low rates of EBF among HIV-negative women with introduction of liquids and other foods prior to 3 months [ 72 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The post-2010 period (Table 3 ) after South Africa endorsed the 2010 WHO infant feeding guidelines for HIV-positive women recommending EBF for 6 months irrespective of HIV status resulted in a wide range of EBF rates among HIV-positive (26–99%) and HIV-negative (12–92%) women [ 64 69 ]. However, EBF duration was brief (1-3 months) [ 66 , 70 , 71 ]. While initiation of breastfeeding was high, there were low rates of EBF among HIV-negative women with introduction of liquids and other foods prior to 3 months [ 72 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mushaphi et al [ 14 ] conducted a study about recommendations for infant feeding policy and programs in Dzimauli region, South Africa. Motadi et al [ 15 ] focused on breastfeeding knowledge and practices among mothers of children younger than two years from a rural area in the Limpopo Province, South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Poor exclusive breastfeeding practice in the current study is due to the fact that most mothers indicated that returning to schools, in uence by the family members and insu cient milk as the main reason for terminating breastfeeding and introducing complementary food. Similarly, several studies have also reported going back to school or work, insu cient breastmilk as the main reasons for introducing complementary foods early [15,24,27,28,29,30,31]. Despite a high level of awareness by health professionals and Department of Health on exclusive breastfeeding, practicing exclusive breastfeeding is still a problem in many rural areas of South Africa.…”
Section: Discussionmentioning
confidence: 99%